2020
DOI: 10.1038/s41386-020-0724-x
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the effects of methylphenidate on the dopaminergic and noradrenergic functional circuits

Abstract: Functional magnetic resonance imaging (fMRI) can be combined with drugs to investigate the system-level functional responses in the brain to such challenges. However, most psychoactive agents act on multiple neurotransmitters, limiting the ability of fMRI to identify functional effects related to actions on discrete pharmacological targets. We recently introduced a multimodal approach, REACT (Receptor-Enriched Analysis of functional Connectivity by Targets), which offers the opportunity to disentangle effects … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 92 publications
(110 reference statements)
2
26
0
Order By: Relevance
“…The resulting maps coherently show high FC values in the core areas of the molecular systems investigated and are in line with the molecular-enriched FC circuits described in previous REACT-based fMRI studies. 23 , 24 , 45 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting maps coherently show high FC values in the core areas of the molecular systems investigated and are in line with the molecular-enriched FC circuits described in previous REACT-based fMRI studies. 23 , 24 , 45 …”
Section: Resultsmentioning
confidence: 99%
“…A detailed explanation of the REACT methodology and its applications can be found elsewhere. 23 , 24 In brief, the functional circuits related to the DAT, NET, SERT and µ-opioid receptor systems were estimated using a two-step multivariate regression analysis 39 , 40 implemented with the fsl_glm command of FSL. In the first step, the rs-fMRI volumes were masked using a binarized mask derived from the molecular atlases to restrict the analysis to the voxels for which the density information of the neurotransmitter was available in the templates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the idea of enriching fMRI with molecular information is not new in human neuroimaging [54][55][56][57] , here we used transcriptomic-neuroimaging mapping to study the effects of an acute pharmacological manipulation on DRN serotonin optogenetic activation. We showed that the SSRI uoxetine evoked bidirectional changes in the effect of optogenetic manipulation on the SRNs.…”
Section: Discussionmentioning
confidence: 99%
“…The application of REACT to clinical and pharmacological blood oxygen leveldependent (BOLD) fMRI studies has demonstrated its ability to uncover new patterns of functional alterations in neurotransmission-related circuits in patients with brain disorders and suggests potential drug-target mechanisms at the system level that could underlie the functional effects of pharmacological treatment (Cercignani et al, 2021; Dipasquale et al, 2020; Dipasquale et al, 2019; Martins et al, 2021; Wong et al, 2021). However, the BOLD signal is an indirect measure of neuronal activity, resulting from the combination of changes in both oxygen consumption and regional cerebral blood flow (CBF), as well as changes in regional blood volume (CBV) (Buxton et al, 2004).…”
Section: Introductionmentioning
confidence: 99%